2016
DOI: 10.3390/ijerph13040437
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behaviours of Preadolescent Children over Time: Stability, Continuity and the Moderating Role of Perceived Parental Feeding Practices

Abstract: The links between childhood eating behaviours and parental feeding practices are well-established in younger children, but there is a lack of research examining these variables in a preadolescent age group, particularly from the child’s perspective, and longitudinally. This study firstly aimed to examine the continuity and stability of preadolescent perceptions of their parents’ controlling feeding practices (pressure to eat and restriction) over a 12 month period. The second aim was to explore if perceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Drawing on evidence of stability among parents of children in early childhood (Farrow & Blissett, 2012) and later childhood (Webber et al, 2010), in conjunction with the present results suggesting stability in middle childhood, we conclude that parents tend to report stability in their use of restrictive feeding and pressure to eat across the childhood years. This is corroborated by another study focused on middle childhood (Mage = 8.7 years), which showed that children also reported stability in their perceptions of their parents' use of pressure to eat and restrictive feeding over 12 months (Houldcroft, Farrow, & Haycraft, 2016). Taken together, this evidence of inter-individual stability suggests that a parent who scores higher than their peers on pressure to eat and restrictive feeding practices will tend to remain higher as their child grows, and a parent who scores lower will tend to remain lower.…”
Section: Stability and Continuity Of Parental Controlling Feeding Prasupporting
confidence: 65%
“…Drawing on evidence of stability among parents of children in early childhood (Farrow & Blissett, 2012) and later childhood (Webber et al, 2010), in conjunction with the present results suggesting stability in middle childhood, we conclude that parents tend to report stability in their use of restrictive feeding and pressure to eat across the childhood years. This is corroborated by another study focused on middle childhood (Mage = 8.7 years), which showed that children also reported stability in their perceptions of their parents' use of pressure to eat and restrictive feeding over 12 months (Houldcroft, Farrow, & Haycraft, 2016). Taken together, this evidence of inter-individual stability suggests that a parent who scores higher than their peers on pressure to eat and restrictive feeding practices will tend to remain higher as their child grows, and a parent who scores lower will tend to remain lower.…”
Section: Stability and Continuity Of Parental Controlling Feeding Prasupporting
confidence: 65%
“…It creates a threat of exceeding the upper level intake (UL) of this ingredient, which in the case of children, may lead to hypercalcaemia, hypercalciuria and kidney problems [ 25 , 26 ]. Children are a special group of potential recipients of supplements due to the fact that: They do not make their own purchasing decisions; They do not make their own decisions concerning diet [ 27 , 28 , 29 ]; They fall victim to unfair marketing practices [ 30 , 31 ]; They have different metabolic processes, which are responsible for biotransformation of active substances (metabolism and elimination), or various ways of the organism reacting to the used preparation [ 32 , 33 , 34 ]; They have very varied dietary requirements [ 35 ]. …”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional and experimental studies have established associations between these feeding practices and increased child preference for restricted foods, heightened responsiveness to the presence of palatable foods, and eating beyond satiety when restricted foods are made available (Galloway, Fiorito, Francis, & Birch, 2006;Jansen et al, 2012). In longitudinal investigations, coercive control feeding practices have been shown to contribute to excessive weight gain (for restriction only) and problematic eating behaviors during childhood and adolescence (Birch, Fisher, & Davison, 2003;Houldcroft, Farrow, & Haycraft, 2016;Hughes, Power, O'Connor, Orlet Fisher, & Chen, 2016;Rodgers et al, 2013). Available evidence suggests that childhood feeding experiences continue to adversely affect individuals' food preferences, dietary habits, and eating behaviors into adulthood (Batsell, Brown, Ansfield, & Paschall, 2002;Brunstrom, Mitchell, & Baguley, 2005;Wadhera, Capaldi Phillips, Wilkie, & Boggess, 2015).…”
Section: Introductionmentioning
confidence: 99%